Quinoa: In Perspective of Global Challenges - Jaikishun, Sirpaul; Li, Wenqiang; Yang, Zhenbiao; Song, Shikui (Agronomy (Basel), 2019)
The global population is on the path of an increasing trajectory with a simultaneous decline in arable land resources through salinization and desertification that have resulted mainly from climate change and other anthropogenic activities. Rising temperatures will cause changes in the entire ecosystem, resulting in significant alterations in global climate paradigms and a threat to food security. This review focuses on how the highly resilient Chenopodium quinoa Willd. can sustainably mitigate some of the detrimental impacts, such as starvation, and support or provide ecosystem services. In comparison, compared with the traditional staple food crops, quinoa has remarkable tolerance to abiotic stresses and is highly nutritious, with a unique balance and higher amounts of nutrients, and can therefore be an important crop for food security and nutritional adequacy. This crop has the potential to ameliorate global challenges with respect to increase in global population, effects of climate change, desalinization, phytoremediation, satisfying nutrient deficiency, and alleviating poverty.